Uso del programa de bioinformática que transforman los informes del banco de datos por homología para la generación de una estructura espacial de proteína - Guardia Jara, Juan Roosvelt (2009)
This study reports the prediction of the folding of the globular polypeptide chain of amino acids that form the tertiary structure of the protein phosducin of the retina of an animal, activated by light radiation during the process of vision. It has used the program of bioinformatics algorithms that transform data reports for approval by the generation of a spatial structure of protein, with the SwissModel and Data "Protein Data Bank", accessible via the Web page as ExPasy server or program DeepView, Swiss pdb-Prospects. Firstly, a model for analysis of amino acids to the primary structure of Phosducin, obtaining a secondary structure composed of eight helices, five sets of beta sheets and beta turns 16. The α helices and β sheets were generated by the polarization effect of amino acids that rotate through the polypeptide chain. Predicted the formation of the tertiary structure of globular protein folding phosducin as compact propellers α, β sheet and turns of the 16 amino acids, originated a greater accumulation of electrons around the globular folding was more likely greater accumulation of the flow of biological information to be transmitted to another protein.